If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1(x + -8) = 0 Reorder the terms: 9x + -1(-8 + x) = 0 9x + (-8 * -1 + x * -1) = 0 9x + (8 + -1x) = 0 Reorder the terms: 8 + 9x + -1x = 0 Combine like terms: 9x + -1x = 8x 8 + 8x = 0 Solving 8 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 8x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 8x = 0 + -8 8x = 0 + -8 Combine like terms: 0 + -8 = -8 8x = -8 Divide each side by '8'. x = -1 Simplifying x = -1
| (45x+58y)+(46x-22y)= | | x-7-4x=28 | | 2d+4+6=-18 | | 2a+a=552 | | 2x-(-16)=44 | | X+45+x+43=76 | | 3=16-4x | | (-4x^2y^5)(9x^2y^4)= | | -5s-4=-39 | | 16n=m | | 4x-6y=-40 | | (37x-29y)+(41x+56y)= | | 5y-8=15y+22 | | (2x+5)(x-5)=7 | | -6-x=4x+6 | | 15=b-a | | 6t+9t=80 | | 20+3b=20 | | 3x^2+15x+27= | | 9x+5y=-35 | | -5x-5=3x+11 | | 234*n=6 | | (-3x^4p^7)(6y^5x^3)= | | 8a^2b^2-32ab= | | z+25=y | | x-7(x-4)=30-5x | | 5-.6x=-6 | | 6x^10+24x^9+48x^8+7x^6+28x^5+56x^4+3x^2+12x+24=0 | | 7w+23=4w+8w-22 | | A(10)=3+(10-1)(7) | | 2x-5(x-2)=-3+4x-36 | | -15+2=18 |